(x+1)(4-x)=6x

Simple and best practice solution for (x+1)(4-x)=6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)(4-x)=6x equation:



(x+1)(4-x)=6x
We move all terms to the left:
(x+1)(4-x)-(6x)=0
We add all the numbers together, and all the variables
(x+1)(-1x+4)-6x=0
We add all the numbers together, and all the variables
-6x+(x+1)(-1x+4)=0
We multiply parentheses ..
(-1x^2+4x-1x+4)-6x=0
We get rid of parentheses
-1x^2+4x-1x-6x+4=0
We add all the numbers together, and all the variables
-1x^2-3x+4=0
a = -1; b = -3; c = +4;
Δ = b2-4ac
Δ = -32-4·(-1)·4
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-5}{2*-1}=\frac{-2}{-2} =1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+5}{2*-1}=\frac{8}{-2} =-4 $

See similar equations:

| -x/3+5=0 | | 5x^2-100x+95=0 | | X=4w+7 | | -4d+9=-39 | | .33(x+5)=2 | | -15=-4v-3 | | 24=1+1/4p | | 3/4r+4=13 | | 3-4(4-2x)=0 | | 5/9n-13=27 | | 3-7(8x+2)=9 | | (2x-5)(x^2+4x-5)=0 | | 10n-0.375=0.1n-0.75 | | 5h+16-7h-8=32 | | 7-7v=-56 | | 6x-48=-6 | | 42/x=54/100 | | 6x-6=-72 | | -4b-6=50 | | 4/3=m/3/5 | | 5m-2=58 | | P2+q=27 | | 6x-18=-48 | | 7x-49=-28 | | 14x=7x-18 | | 7x+70=-77 | | 0=-16t^2+80t+40 | | 3r+15=42 | | 3x+50=2x+200 | | 1.25=300/x | | x=|25-37| | | 6/x-4=3/x-5 |

Equations solver categories